Пути коррекции инсулинорезистентности. Роль бишофита = Ways of correction of insulin resistance - Dragomiretska, N. V.; Zabolotna, I. B.; Gushcha, S. G. (Journal of Education, Health and Sport, 2015)
Dragomiretska N. V., Zabolotna I. B., Gushcha S. G. Пути коррекции инсулинорезистентности. Роль бишофита = Ways of correction of insulin resistance. The role of bishofite. Journal of Education, Health and Sport. 2015;5(9):663-670. ISSN 2391-8306. DOI10.5281/zenodo.31762 http://dx.doi.org/10.5281/zenodo.31762 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A663-670 https://pbn.nauka.gov.pl/works/642311 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. ПУТИ КОРРЕКЦИИ ИНСУЛИНОРЕЗИСТЕНТНОСТИ. РОЛЬ БИШОФИТА WAYS OF CORRECTION OF INSULIN RESISTANCE. THE ROLE OF BISHOFITE Н. В. Драгомирецкая, И. Б. Заболотная, С. Г. Гуща N. V. Dragomiretska, I. B. Zabolotna, S. G. Gushcha Государственное учреждение «Украинский научно-исследовательский институт медицинской реабилитации и курортологи МЗ Украины», Одесса State Institution «Ukrainian Scientific Research Institute of Medical Rehabilitation and Resort Therapy of the Ministry of Health of Ukraine», Odessa Abstract The state of insulin resistance was reproduced in white Wistar rats by injection of alloxan in the original dosage. This state was characterized by increased level of glucose during glucose tolerance test. Two-week internal application of aqueous solution of Poltava bishofite prevented disruption of the basal level of glucose in the blood of rats. The obtained data served as an experimental justification of application of bishofite in clinical practice on patients with the syndrome of insulin resistance affected by nonalcoholic fatty liver disease. Decrease in concentration of total cholesterol, triglycerides and tendency to decrease in low density lipoprotein were noted after one month of application of the Poltava bishofite by these patients. Glucose level of the blood serum in the treatment process did not change significantly but insulin level decreased significantly, i.e. effectiveness of insulin activity increased. This resulted in a decrease of HOMA-IR index especially for patients with baseline hyperinsulinemia with insulin level decreasing in 1.6 times during treatment. Keywords: aqueous solution of Poltava bishofite, insulin resistance. Реферат У белых крыс линии Вистар было воспроизведено состояние инсулинорезистентности путем введения аллоксана в оригинальной дозировке. Это состояние характеризовалось повышением уровня глюкозы при проведении теста толерантности к глюкозе. Двухнедельное внутреннее применение водного раствора Полтавского бишофита предотвращало нарушение базального уровня глюкозы в крови крыс. Полученные данные послужили експериментальным обоснованием применения бишофита в клинической практике у больных с синдромом инсулинорезистентности на фоне неалкогольной жировой болезни печени. У этих больных после месячного приема Полтавского бишофита было установлено уменьшение концентрации общего холестерина, триглицеридов, тенденция к уменьшению липопротеидов низкой плотности. Уровень глюкозы сыворотки крови в процессе лечения существенно не изменился, но уровень инсулина значительно снизился, т.е., эффективность инсулиновой активности повысилась. Это привело к снижению индекса НОМА-IR особенно у больных с исходной гиперинсулинемией, у которых уровень инсулина в процессе лечения снизился в 1,6 раза. Ключевые слова: водный раствор Полтавской бишофит, резистентность к инсулину.